2022
DOI: 10.3390/ijms231911761
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of High-Temperature Requirement Protein A2 Protease Activity Represses Myogenic Differentiation via UPRmt

Abstract: Skeletal muscles require muscle satellite cell (MuSC) differentiation to facilitate the replenishment and repair of muscle fibers. A key step in this process is called myogenic differentiation. The differentiation ability of MuSCs decreases with age and can result in sarcopenia. Although mitochondria have been reported to be involved in myogenic differentiation by promoting a bioenergetic remodeling, little is known about the interplay of mitochondrial proteostasis and myogenic differentiation. High-temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…HtrA2/Omi deficiency promotes the generation of unfolded proteins, in particular components of respiratory complexes on mitochondrial membranes. The current study shows that HtrA2/Omi protease deficiency leads to oxidative phosphorylation and a reduction in the number of mitochondrial genes encoding ETC subunits [14]. Moisoi et al showed that an increase in the unfolded subunits of the HtrA2/Omi KO brain mitochondrial complexes I-IV leads to systemic respiratory dysfunction [42].…”
Section: Oxphos Complex Abnormalities Promote Pro-inflammatory Macrop...mentioning
confidence: 54%
See 1 more Smart Citation
“…HtrA2/Omi deficiency promotes the generation of unfolded proteins, in particular components of respiratory complexes on mitochondrial membranes. The current study shows that HtrA2/Omi protease deficiency leads to oxidative phosphorylation and a reduction in the number of mitochondrial genes encoding ETC subunits [14]. Moisoi et al showed that an increase in the unfolded subunits of the HtrA2/Omi KO brain mitochondrial complexes I-IV leads to systemic respiratory dysfunction [42].…”
Section: Oxphos Complex Abnormalities Promote Pro-inflammatory Macrop...mentioning
confidence: 54%
“…HtrA2/Omi is located in the mitochondrial membrane gap and was originally described as a serine protease that induces stress responses in mammalian cells [12]. Previous studies have mostly focused on the potential regulation of apoptosis by HtrA2/Omi proteins in neurodegenerative diseases [13], sarcopenia [14], and tumors [15]. With the progress of research, another role of HtrA2/Omi proteins in cells has been gradually discovered, as a key regulator of mitochondrial molecular quality control [16].…”
Section: Introductionmentioning
confidence: 99%
“…HtrA2 is a protease located in the mitochondrial IMS that is involved in UPRmt to maintain mitochondrial homeostasis (Riar et al, 2017). Previously published results from our team (Sun et al, 2022) showed that inhibition of HtrA2 enzyme activity using UCF101 resulted in blocked differentiation of C2C12 myoblasts. Considering that the loss of HtrA2 enzyme activity-induced proteostasis imbalance and mitochondrial IMS stress are the main triggers of UPRmt, we hypothesised that UPRmt could be associated with impaired differentiation due to HtrA2 enzyme activity inhibition.…”
Section: Uprmt and Myogenic Differentiationmentioning
confidence: 99%
“…MRFs also regulate the level of myosin heavy chain (MyHC), which determines the contractile properties of myofibers (Zammit, 2017). Reduced myogenic differentiation capacity has been reported to be associated with the progression of several muscle diseases, such as sarcopenia (Sun et al, 2022), skeletal muscle atrophy (Rahman and Quadrilatero, 2023) and Duchenne muscular dystrophy (Meyer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation